Developing an Inquiry -Based Learning (IBL) to Enhance Learners’ Engagement in a Research Methodology Course - Shapii, Aspalila; Bukhari, Nurliyana (UUM, 2021)
Lecturers teaching research methodology courses often feel concerned when discovering many students attempted research without the necessary research methodology skills even after completing compulsory faculty-organized research methodology (RM) courses. The lack of research knowledge and skills is evident when the submitted research proposal deemed not robust enough to qualify for a feasible study. Scholars identify lack of deep learning during RM courses as the main factor since the courses are perceived as not having context and uninteresting hence there was little engagement with the material. Inquiry-based Reflective Learning (IBRL) has been argued to effectively rectify this as its pedagogies involve students in discovery and employ approaches to learning that are essentially student-led. IBRL requires students to use questioning and researching to discover, analyze, communicate, and reflect on information, which can help teachers meet various learning goals. In the study, inquiry-based instruction was used to encourage students to develop multiple perspectives and encourages empathy with the subject and eventually enhance engagement. The study involves a reflective cases study study of research methodology courses to explore the lecturer’s classroom practice using IBRL and the students’ experiences participating in IBRL activities. The methodology used involves conducting a needs analysis via Google Form survey, interviewing and document analysis of the lecturers’ teaching plans and field notes and the reflections by both the lecturers and students. The findings from the survey indicate that most students admit they have minimal research skills and require assistance particularly practical research skills. Data from the reflections and field notes also show that students feel engaged with discovery activities conducted, while the lecturer feels students understand better and are more engaged with IBRL activities conducted. The study has shed significant input on the needs of RM students, participants’ experiences, and the challenges of implementing RM courses using IBRL. Some recommendations to facilitate more deep learning experiences among postgraduate students taking RM courses are also proposed.